2022
DOI: 10.1002/ajh.26595
|View full text |Cite
|
Sign up to set email alerts
|

TP53‐altered chronic lymphocytic leukemia treated with firstline Bruton's tyrosine kinase inhibitor‐based therapy: A retrospective analysis

Abstract: Long-term follow up of prospective studies has shown that continuous Bruton's tyrosine kinase inhibitor (BTKi) therapy leads to durable remissions in previously untreated patients with TP53-altered chronic lymphocytic leukemia (CLL); however, it is unknown how variant allele frequency (VAF) of TP53 mutation (TP53-m) or percentage of cells with deletion of chromosome 17p [del(17p)] influences efficacy of firstline BTKi. We performed a retrospective analysis of 130 patients with CLL with baseline del(17p) and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…65 In a recent retrospective study on 130 patients with TP53 dysfunction who had received BTKi with or without venetoclax and with or without CD20 antibody in the firstline setting, the authors reported good 4-year outcomes, with very good outcomes for patients treated with doublets or triplets. 66 In addition, the authors also suggest that low-burden TP53 alterations should not be ignored, a finding that is in line with the recently published study. 67 The CLL16 trial is currently recruiting patients with high risk CLL exhibiting a complex karyotype or a del17p/mut TP53 68 and was set up to compare venetoclax-obinutuzumab to the triple combination with venetoclax-obinutuzumab plus acalabutinib over 14 months and 10 more cycles of acalabrutinib in case of detectable MRD (NCT05197192).…”
Section: Firstline Treatment In Patients With Del17p/muttp53supporting
confidence: 80%
See 1 more Smart Citation
“…65 In a recent retrospective study on 130 patients with TP53 dysfunction who had received BTKi with or without venetoclax and with or without CD20 antibody in the firstline setting, the authors reported good 4-year outcomes, with very good outcomes for patients treated with doublets or triplets. 66 In addition, the authors also suggest that low-burden TP53 alterations should not be ignored, a finding that is in line with the recently published study. 67 The CLL16 trial is currently recruiting patients with high risk CLL exhibiting a complex karyotype or a del17p/mut TP53 68 and was set up to compare venetoclax-obinutuzumab to the triple combination with venetoclax-obinutuzumab plus acalabutinib over 14 months and 10 more cycles of acalabrutinib in case of detectable MRD (NCT05197192).…”
Section: Firstline Treatment In Patients With Del17p/muttp53supporting
confidence: 80%
“…In a recent retrospective study on 130 patients with TP53 dysfunction who had received BTKi with or without venetoclax and with or without CD20 antibody in the firstline setting, the authors reported good 4‐year outcomes, with very good outcomes for patients treated with doublets or triplets 66 …”
Section: Firstline Treatment In Patients With Del17p/muttp53mentioning
confidence: 99%
“…This should be ascertained using (a) CLL FISH panel to look for evidence of del17p13 and (b) Sanger sequencing or next-generation sequencing panel to evaluate for TP53 mutations, with a cutoff of at least 10%. It is important to obtain both these tests since ~3-5% of patients will harbor a deleterious TP53 mutation on DNA sequencing in the absence of del17p13 on CLL FISH, and multiple studies have shown these patients have equally poor outcomes [23][24][25][26][27].…”
Section: Management Of the Patient With Previously Untreated Cll Pati...mentioning
confidence: 99%
“…Additionally, substantial differences in progression-free survival or overall survival were linked to the amount of TP53 changes [21] . According to Cherng et al [21] , in the era of targeted medicine, low-burden TP53 mutations should not be disregarded when determining the genetic risk of CLL. The variable allele frequency threshold may also have significant effects on how clinically CLL is managed .…”
Section: Discussionmentioning
confidence: 99%